(untitled) (Plant Tissue Culture and Biotechnology, 2017)
Effects of cytokinins were studied on multiple shoot regeneration in Inula royleana DC. Callus from leaf of I. royleana was treated with different concentrations of BAP and in order to find out the limiting concentrations of both BAP and Kn at which maximum shoot regeneration took place. Among different concentrations 1 mg/l BAP and 0.8 mg/l Kn proved to be optimum. Rooting was obtained in White’s medium. Regenerated plantlets were successfully acclimatized in pots containing vermicompost. Plant Tissue Cult. & Biotech. 27(2): 189-194, 2017 (December)